Improving airport services using sentiment analysis of the websites. (April 2017) - Gitto, Simone; Mancuso, Paolo
Abstract: Measuring the level of customer satisfaction of airport passengers provides a valuable feedback to airport managers. In fact, researchers and practitioners alike have recognized that measuring airport performance through purely operational approaches is not sufficient. In order to overcome such weakness a growing literature on airport performance measurement has focused its attention on models assessing passengers' needs and their perception of the airport service quality. The developed models vary according to the type of decisions supported, evaluation perspective, type of measurements, and evaluation approach used. Departing from the above literature, the present paper explores the possibility offer by data collected in the blogs and by the text extracting software for assessing the level of services perceived by airport customers. The paper identifies the strengths, weakness and synergies of the proposed approach in assessing users' perceptions of the quality of airport services. Highlights: The paper investigates the level of customer satisfaction of airport services. It uses sentiment analysis based on blog data. The sample is based upon five major European airports. Most of passenger opinions concern food & drink and shop services.